Blood coagulation at the site of microvascular injury in healthy and coumadin-treated subjects heterogenous for factor V Leiden mutation - Undas, Anetta; Brzezinska-Kolarz, Beata; Orfeo, Tom; Brummel-Ziedins, Kathleen; Musial, Jacek; Szczeklik, Andrew; Mann, Kenneth G. (Thrombosis and Haemostasis, 2007)
There is little knowledge regarding the in-vivo course of coagulation reactions in subjects with factor (F)V Leiden (G1691A, R506Q). The aim of the current study was to evaluate the effect of FV Leiden on coagulant reactions triggered by vascular injury. At the site of microvascular injury, prothrombin activation and FVa formation and inactivation have been evaluated in 16 apparently healthy subjects and 16 patients on long-term anticoagulation with acenocoumarol, with eight heterogenous carriers of FV Leiden in the healthy and in the anticoagulated group. Thrombin formation, measured by levels of thrombin-antithrombin complexes (TAT) and thrombin B-chain, proceeded at similar rates in the bleeding-time blood in carriers and non-carriers of FV Leiden. The onset and rate of FV activation did not differ significantly among the four groups. When healthy carriers of FV Leiden were compared to healthy non-carriers, the onset of FVa inactivation by activated protein C (APC) was delayed by 60 to 90 seconds (p=0.01). Anticoagulated individuals also showed the same pattern of FV Leiden associated differences in the time of occurrence of the 30 kD FVa heavy-chain fragment (p=0.021). Our results indicate that when blood clotting is triggered by microvascular injury, the heterozygous expression of FV Leiden has no effect on thrombin generation in healthy or coumadintreated subjects. Inactivation of FVa by theAPC mechanism is attenuated significantly in carriers of FV Leiden but the magnitude of this effect is smaller than that observed in most purified systems.
Keywords: Coagulation; factor V Leiden; oral anticoagulants; thrombin generation